A place of belonging : five founding women of Fairbanks, Alaska - Movius, Phyllis Demuth (University of Alaska Press, 2009)
Alaska has always attracted people from varied backgrounds. In A Place of Belonging, Phyllis Movius introduces us to five women who settled in Fairbanks between 1903 and 1923 and who typify the disparate population that has long enriched Alaska. The women's daily lives and personal stories are woven together in these biographical portraits, drawn from the women's letters, memoirs, personal papers, club records, their own oral histories and published writings. Enriched by many never-before-published historical photos, Movius's research gives us a unique inroad into life on the frontier.